The rate of nonunion in the MRI-detected occult scaphoid fracture: a multicentre cohort study - Dean, BJF; Riley, N; Little, C; Sheehan, W; Gidwani, S; Brewster, M; Dhiman, P; Costa, ML (British Editorial Society of Bone and Joint Surgery, 2024)
Aims There is a lack of published evidence relating to the rate of nonunion seen in occult scaphoid fractures, diagnosed only after MRI. This study reports the rate of delayed union and nonunion in a cohort of patients with MRI-detected acute scaphoid fractures.